2012
DOI: 10.5010/jpb.2012.39.4.261
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of plant responses to sound waves in Arabidopsis

Abstract: Environmental factors greatly influence the growth, development, and even genetic characteristics of plants. The mechanisms by which sound influences plant growth, however, remain obscure. Previously, our group reported that several genes were differentially regulated by specific frequenciesof sound treatmentusing a sound-treated subtractive library. In this study, we used a proteomic approach to investigate plant responses to sound waves in Arabidopsis. The plants were exposed to 250-Hz or 500-Hz sound waves,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Besides RuBisCO, we also noticed strong up-regulation of LHCB2 transcript, which encodes a light harvesting complex playing critical role in providing energy required for photolysis. While LHCB protein mainly showed down-regulation, it is in agreement to the previous findings 51 . Strong up-regulation in Ferredoxin-NADP + reductase (FNR) was marked in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides RuBisCO, we also noticed strong up-regulation of LHCB2 transcript, which encodes a light harvesting complex playing critical role in providing energy required for photolysis. While LHCB protein mainly showed down-regulation, it is in agreement to the previous findings 51 . Strong up-regulation in Ferredoxin-NADP + reductase (FNR) was marked in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Protein extraction, 2-DGE, in-gel digestion, identification and functional classification were conducted as previously described by Kwon, et al . 51 . Briefly, protein was extracted from rosette using TCA/acetone/phenol extraction method and concentration was determined by 2D-Quant kit (GE Healthcare Life Sciences, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Increased photosynthetic ability has been observed in strawberry and rice in response to sound treatment ( Qi et al, 2009 ; Meng et al, 2012 ; Jeong et al, 2014 ) ( Table 1 ). Proteomics analysis showed that photosynthesis-related proteins were highly expressed at 8 h after 250 or 500 Hz sound exposure in Arabidopsis ( Kwon et al, 2012 ) ( Table 1 ). Since sound energy induced secondary products can make chemical energy, sound treatment is thought to improve photosynthesis ( Meng et al, 2012 ).…”
Section: Application Of Sound Waves To Improve Plant Healthmentioning
confidence: 99%
“…Even if the emission of the sounds is entirely involuntarily, and is merely a result of the plant's physiological condition, nearby organisms that are capable of hearing the sounds could eavesdrop for their own benefit. Furthermore, some of these responses may be beneficial for the emitting plant, for example if the plant's sounds induce resistance to drought or disease [29][30][31][32] in neighboring plantsor even in other parts of the same plant. In such cases, plant sound emission and perception would be favored by natural selection.…”
Section: Introductionmentioning
confidence: 99%